2023
DOI: 10.1111/wre.12575
|View full text |Cite
|
Sign up to set email alerts
|

Three‐way fungal interactions affect the potential biological control of Himalayan balsam, Impatiens glandulifera

Abstract: Himalayan balsam (Impatiens glandulifera) is one of the most invasive weeds across Europe. The rust fungus, Puccinia komarovii var. glanduliferae has been introduced as a biological control agent, but success has been patchy. Here, we investigated whether mycorrhizal and endophytic fungi can affect rust efficacy and plant growth. Over three experiments, we found that AM fungi and the rust alone or together consistently reduced plant growth, but this depended on the identity of species in the AM inoculum. Meanw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In this study, mycorrhizal fungal inoculation decreased the biomass of balsam when it was grown alone, but tended to increase it when it was grown in both inter- and intraspecific competition. In previous work, the Symbio inoculum has proven to be consistently antagonistic to I. glandulifera [ 18 , 36 ]. Furthermore, there appears to be a negative relation between colonisation levels in the field and plant size when the plant is invasive in the UK, but not where it is native, in the Himalayas [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, mycorrhizal fungal inoculation decreased the biomass of balsam when it was grown alone, but tended to increase it when it was grown in both inter- and intraspecific competition. In previous work, the Symbio inoculum has proven to be consistently antagonistic to I. glandulifera [ 18 , 36 ]. Furthermore, there appears to be a negative relation between colonisation levels in the field and plant size when the plant is invasive in the UK, but not where it is native, in the Himalayas [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that some endophytes were found only when AM fungi were added while others disappeared with AM inoculation does suggest that there are interactions between the fungal groups within the plant. It has recently been found that the addition of the Symbio inoculum to I. glandulifera can increase or decrease the abundance of certain endophytes [ 36 ]. Clearly, the fungal identity and experimental location are likely to be two critical factors determining the outcome of future experiments involving these fungi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations